The ethics of knowledge sharing: a feminist examination of intellectual property rights and open-source materials in gender transformative methodologies - Goldmann, Leah; Welbourn, Alice; Gillespie, Diane; Ghebrebhran, Nastnet; Barro, Lufuno; Siebert, Sara; Kagoya, Hawa; Michau, Lori; Kohli, Anjalee; Musuya, Tina; Kusiima, Sonia Rebecca (Frontiers in Research Metrics and Analytics, 2024)
Debates on intellectual property rights and open source frequently stem from the business sector and higher education, where goals are typically oriented toward profit, academic status, credit, and/or reputation. What happens if we reconsider the ethics of intellectual property rights and open source when our driving motivation is advancing women's health and rights? How does this prioritization complicate our assumptions of copyright and open access? How can we embark on a journey that validates the complex realities of multiple stakeholders who have good intent, but do not always consider the unintended impacts and the broader power dynamics at play? This paper explores the tensions and nuances of sharing methodologies that aim to transform harmful gender norms in an ecosystem that does not always consider the complex challenges behind intellectual property and opensource material. As a thought-collective dedicated to using a feminist approach to unpack and promote the principles of ethical, effective, and sustainable scale, we hope to underscore how the current research and debates on intellectual property rights and open-source material have good aims but may also fall short in encompassing the realities of gendered social norms change in and with communities around the world. We conclude with key recommendations for donors, researchers, International Development Corporations, International Non-Governmental Organizations, and those interested in using or adapting dynamic, gender transformative materials created by others.